Assembly of Ferrocene Molecules on Metal Surfaces Revisited - Ormaza, Maider (2015)
Metallocene (MCp2) wires have recently attracted considerable interest in relation to molecular spintronics due to predictions concerning their half-metallic nature. This exciting prospect is however hampered by the little and often-contradictory knowledge we have concerning the metallocene self-assembly and interaction with a metal. Here, we elucidate these aspects by focusing on the adsorption of ferrocene on Cu(111) and Cu(100). Combining low-temperature scanning tunneling microscopy and density functional theory calculations, we demonstrate that the two-dimensional molecular arrangement consists of vertical- and horizontal-lying molecules. The noncovalent T-shaped interactions between Cp rings of vertical and horizontal molecules are essential for the stability of the physisorbed molecular layer. These results provide a fresh insight into ferrocene adsorption on surfaces and may serve as an archetypal reference for future work with this important variety of organometallic molecules.